Chapter 11. Computers in Market Analysis (Computer Aided Drug Development, 2024)
AuthorMrs. Mansi SinhaAssistant Professor, Department of Pharmacology, IIMT College of Pharmacy, Greater Noida, Uttar Pradesh, IndiaAbstractComputational technologies have revolutionized market analysis by enabling sophisticated data processing, pattern recognition, and predictive modeling capabilities. Advanced computing systems process vast amounts of market data in real-time, identifying trends and patterns through machine learning algorithms and artificial intelligence. Market analysts utilize big data analytics to gain deeper insights into consumer behavior, while automated systems execute complex trading strategies based on algorithmic decisions. Social media analytics and sentiment analysis provide immediate feedback on market reactions and consumer preferences, allowing businesses to adapt strategies rapidly. Visualization tools transform complex data into actionable insights, enhancing decision-making processes across organizations. Real-time processing capabilities enable immediate response to market changes, while predictive analytics forecast future trends with increasing accuracy. The integration of artificial intelligence with traditional market analysis methods has created new opportunities for understanding market dynamics and consumer behavior. However, challenges persist in data quality management, algorithmic bias mitigation, and balancing automated analysis with human interpretation. Success in modern market analysis requires combining computational power with human expertise to generate meaningful insights and strategic advantagesKeywords: Market Analysis; Computational Finance; Data Analytics; Predictive Modeling; Machine Learning; Business Intelligence; Market TrendsView PDF